PENGARUH PEMBERIAN VITAMIN C, VITAMIN E, DAN KROMIUM (CR3+) TERHADAP KADAR INSULIN TIKUS WISTAR YANG DIINDUKSI ALOKSAN - Anugrah Linda Mutiarani (UNUSA Press, 2017)
Objective: To analyze the effect of vitamin C, vitamin E, and chromium (Cr3+) on insulin levels Wistar ratswere induced alloxan.Materials and Methods: This study is an experimental laboratory. Using rats typeWistar strain Rattus novergicus for 6 weeks with a number of 20 head. The independent variables consist of 5treatment groups namely normal diet, normal diet + 1 g/hr chromium, normal diet + 2 mg/day of vitamin C,normal diet + 0.5 mg/day of vitamin E, normal diet + 1 g/hr chromium + 2 mg/day of vitamin C + 0.5mg/day of vitamin E. The dependent variable is the level of insulin. To know the differences of eachtreatment used statistical tests One Way ANOVA, followed by Tukey HSD Post Hoc test withp<0.05.Results: There were significant differences in insulin levels (p<0.05) in the control group, 1, 2, and 4.But in the control group and the group 3 there are no significant differences in insulin levels (p=0.145).Conclusion: Delivery of chromium (treatment 1), vitamin C (treatment 2), and a mixture of chromium,vitamin C, vitamin E (treatment 4) effect on insulin levels, while administration of vitamin E (treatment 3)alone had no effect on insulin levels